Agrammatism in Tagalog: voice and relativisation. Issue 5 (4th May 2018) - Bondoc, Ivan Paul; O'Grady, William; Deen, Kamil; Tanaka, Nozomi
ABSTRACT: Background : Virtually nothing is known about the ability of Tagalog speakers with agrammatic aphasia to cope with basic grammatical features of their language. Tagalog is unusual in exhibiting competing transitive patterns thanks to a system of voice that can make either of the verb's arguments syntactically prominent – a prerequisite for undergoing syntactic operations such as relativisation. Aims : Our objective is to investigate the nature of the syntactic impairment associated with agrammatic aphasia in Tagalog, with special attention to voice patterns and relative clauses (RCs). Methods and Procedures : Five native Tagalog-speaking patients diagnosed with agrammatism took part in (1) elicited-production and (2) comprehension tasks to assess their ability with respect to voice patterns and (3) elicited-production, (4) imitation, and (5) comprehension tasks to assess their performance on RCs. Outcomes and Results : Although the participants did poorly on grammatical morphemes, the classic symptom of agrammatism, their impairment was somewhat less severe in patterns involving verb–agent–patient order, the patient-voice in declarative clauses, and the agent voice in RCs. Conclusions : Our findings reveal a departure from a general cross-linguistic tendency to favour agent-prominent constructions (e.g., the active voice in languages like English), as shown by the participants' greater accuracy on patient voice declaratives than on their agent voice counterparts. Nonetheless, we found evidence of a subject preference in RCs, consistent with reports of a similar advantage in many other languages.